Combination of platelet-rich plasma and bone marrow mesenchymal stem cells enhances tendon–bone healing in a rabbit model of anterior cruciate ligament reconstruction. Issue 1 (December 2016) - Teng, Chong; Zhou, Chenhe; Xu, Danfeng; Bi, Fanggang
Abstract Background The objective of this study was to investigate the potency of platelet-rich plasma (PRP) combined with bone marrow mesenchymal stem cells (BMSCs) to promote tendon–bone healing in a rabbit model. Methods In the in vitro study, the effects of PRP on osteogenic induction of BMSCs were analysed. Later, PRP with or without BMSCs was used in the rabbit model of anterior cruciate ligament reconstruction. Specimens were harvested 8 weeks postoperatively to evaluate tendon–bone healing by histology, radiology, and biomechanical testing. Results The in vitro study revealed that collagen I, osteocalcin, and osteopontin expression was higher in BMSCs co-cultured with PRP for 14 days. The in vivo study revealed a more mature tendon–bone interface using light microscopy, a more newly formed bone at the bone tunnel walls detected by micro-computed tomography, and a significantly higher failure load as assessed by biomechanical testing in the BMSC + PRP group than in the control and PRP groups. Conclusions These results indicate that the combination of PRP and BMSCs promotes tendon–bone healing and has potential for clinical use.